Spectrum of Hematological and Non-Hematological Diseases on Bone Marrow Examination-A Study on 220 Cases at a Tertiary Care Centre - Fatima Rauf, Nowera Zafar, Hira Asif, Atifa Shoaib , Fatima Rauf, Nowera Zafar, Hira Asif, Atifa Shoaib (Journal of Rawalpindi Medical College, 2021)
Background: Bone marrow examination is an invaluable tool in the diagnosis of hematological and non-hematological diseases. Referral is made based on the clinical after analyzing CBC and peripheral film. Objective: This study aims at evaluating the spectrum of diseases diagnosed on bone marrow biopsy at a tertiary care hospital of Rawalpindi, Pakistan. Materials and Methods: This descriptive, cross-sectional study was carried out at the pathology department of Holy family hospital for a duration of 1 year after ethical approval from IRF. All 220 cases requiring bone marrow examination were included in the study by consecutive sampling technique. Variables like age, gender, presenting complaints, examination findings, CBC, peripheral blood film, indications and diagnosis of bone marrow examination were noted. Data was analyzed using SPSS v22. Results: Mean age was 29.15±20.9 years. 117(53.2%) specimens were of males and 103(46.8%) were of females. Spectrum of hematological and non-hematological diseases found on bone marrow examination ranged from acute leukemia in 37(16.8%), megaloblastic anemia in 29(13.1%).The relationship between indications of referral and diagnosis of bone marrow examination was found to be statistically significant showing that suspected diagnosis made by the clinician was same as the final diagnosis in many cases. Pancytopenia was found major indication in most diseases (32.7%). Conclusion: Bone marrow examination is a useful tool in ascertaining diagnosis of various hematological and non-hematological disorders. Pancytopenia was found to be major indication whereas, acute leukemia and megaloblastic anemia were most common malignant and benign hematological disorders on bone marrow examination, respectively.